Helping Leads to Happiness: The Mediating Role of Self-Esteem between Internet Altruistic Behavior and Subjective Well-Being among Emerging Adults - Eli Prasetyo; Agnes Maria Sumargi; Angelina Immaculata Marvin (Psikostudia : Jurnal Psikologi, 2026)
In the digital era, internet use among emerging adults continues to rise, with both positive and negative impacts on their subjective well-being (SWB). Similar to real-world settings, selfless helping behavior (altruism) in the virtual environment can positively affect individual well-being. However, the underlying mechanisms linking internet altruism and SWB among emerging adults in Indonesia remain largely unexplored. Given the close association between self-esteem and altruism, this study aims to examine the mediating role of self-esteem in the relationship between internet altruistic behavior (IAB) and SWB. Participants were 173 emerging adults aged 18-25 years who were active internet users. The survey included scales measuring IAB, self-esteem, life satisfaction (cognitive SWB), and positive and negative affect (affective SWB). Mediation analysis revealed that self-esteem significantly mediates the relationship between IAB and cognitive SWB. However, it did not mediate the relationship between IAB and affective SWB. Furthermore, IAB demonstrated a direct effect on both SWB components. These findings highlight the importance of encouraging emerging adults to engage in online altruistic behaviors to achieve optimal SWB.Di era teknologi, penggunaan internet oleh dewasa muda semakin meningkat. Dampak yang ditimbulkan dapat bersifat negatif ataupun positif bagi kesejahteraan subjektif individu (subjective well-being atau SWB). Seperti halnya dalam dunia nyata, perilaku menolong tanpa pamrih (altruisme) di dunia maya dapat menimbulkan dampak positif bagi kesejahteraan individu. Namun, mekanisme hubungan antara altruisme di internet dengan SWB pada individu dewasa muda di Indonesia belum banyak diketahui. Mengingat harga diri dapat mempengaruhi altruisme, penelitian ini bertujuan untuk menguji peran harga diri sebagai mediator antara perilaku altruisme di internet (internet altruistic behavior atau IAB) dengan SWB. Partisipan dalam penelitian ini adalah 173 orang dewasa muda berusia 18-25 tahun yang merupakan pengguna aktif media internet. Survei yang dibagikan berisikan skala yang mengungkap IAB, harga diri, kepuasan hidup (SWB kognitif), serta afeksi positif dan afeksi negatif (SWB afektif). Hasil analisis mediasi menunjukkan bahwa harga diri menjadi mediator yang signifikan antara IAB dan SWB kognitif, tetapi harga diri tidak memperantarai IAB dan SWB afektif. IAB justru memiliki pengaruh langsung terhadap kedua komponen SWB. Hal ini berimplikasi pada pentingnya mendorong para dewasa muda untuk melakukan perilaku altruisme dalam dunia maya agar dapat mencapai kesejahteraan subjektif yang optimal.